2020
DOI: 10.3390/ani10112105
|View full text |Cite
|
Sign up to set email alerts
|

D-Lactate Increases Cytokine Production in Bovine Fibroblast-Like Synoviocytes via MCT1 Uptake and the MAPK, PI3K/Akt, and NFκB Pathways

Abstract: Acute ruminal acidosis (ARA) is caused by the excessive intake of highly fermentable carbohydrates, followed by the massive production of D-lactate and the appearance of neutrophilic aseptic polysynovitis. Bovines with ARA develop different lesions, such as ruminitis, polioencephalomalacia (calves), liver abscess and lameness. Lameness in cattle with ARA is closely associated with the presence of laminitis and polysynovitis. However, despite decades of research in bovine lameness as consequence of ruminal acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 93 publications
(142 reference statements)
0
37
0
Order By: Relevance
“…The evidence suggest that lactate would be involved in the pathophysiology of lameness in cattle (14). In fact, D-lactic acidosis has been closely associated with the appearance of laminitis and polysynovitis (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence suggest that lactate would be involved in the pathophysiology of lameness in cattle (14). In fact, D-lactic acidosis has been closely associated with the appearance of laminitis and polysynovitis (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study demonstrated that inactivation of the NF-κB pathway strongly decreased mRNA levels of IL-6 induced by Dlactate and bTNF-α in exposed bFLS. Recently, we demonstrated that D-lactate and bTNF-α induced the degradation of IκBα after 30 min of stimulation in bFLS, and treatment with BAY 11-7082 significantly reduced the expression and secretion of IL-6 and IL-8 induced by both stimuli, supporting that the NF-κB pathway is induced by D-lactate in bFLS (23). The NF-κB activity was also shown to be key for the expression of several pro-inflammatory cytokines in bovines, including IL-6, TNF-α, and IL-1β (83)(84)(85)(86)(87).…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, the inhibition of HIF-1 also significantly decreased extracellular secretion of IL-6 induced by D-lactate and bTNF-α ( Figure 7B ). Since D-lactate and bTNF-α also increased the mRNA expression and secretion of IL-8 ( 23 ), we assessed the involvement of HIF-1 in this pro-inflammatory response. However, preincubation with YC-1 did not decrease the IL-8 expression or secretion ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations